Strengthening public pensions and health coverage in the Pacific. (Metro Manila, Philippines Asian Development Bank, 2017)
While the working-age populations for most of the Pacific are rising, the demographic dividend is not fully realized as workforce participation is relatively low. This, coupled with an increasing percentage of older persons in their populations that need support for living and health-care costs, puts additional pressure on the nascent public pension systems that already face challenges around sustainability, coverage, and adequacy. Furthermore, underdeveloped capital markets have limited the spread of private pensions with some Pacific economies relying on culturally informal old age support systems. Strengthening pensions systems in the Pacific and exploring reform options are a pressing public policy issue.
Keywords: Social rights -- Developing countries; Sustainable development; Electronic books